Glutathione transferases - Morgenstern, Ralf (Henry Stewart Talks, 2007)
Isoform properties, Functional significance, Protection from toxicity and genotoxicity, Gene knock-out models, Oxidative stress and cytostatic drugs, Pharmacogenetics, Biochemical transformations in catabolism, Signalling events, Biosynthesis of endogenous lipid mediators, Prostaglandin and leukotriene pathways
Reviewed at 2015/10/01